Spectrum of Secondary Glomerular Diseases in Adult Nephrotic Syndrome - Devarasetty Shashank; Mohini Singh; S.R. Ramakrishnan (Journal of Krishna Institute of Medical Sciences University, 2020)
Background: In developing countries like India, the causes for end stage renal failure has been changing with glomerular diseases occupying an important place. The trend of various primary and secondary causes of Nephrotic Syndrome (NS) over the past few decades has been debatable especially with reference to geographical locations. Aim and Objectives: This study was intended to find out the histologic patterns of glomerular disease associated with NS in South India and analyze the corresponding clinical and biochemical abnormalities associated with these conditions. Material and Methods: One hundred eighty eight patients in the age group of 18-80 years with NS who underwent renal biopsy between the period from1stJanuary 2018 to 30thSeptember 2019 were included in this study. Baseline investigations and other investigations related to renal profile evaluation including complement levels and HIV antibody were done. Results: Focal Segmental Glomerulosclerosis (FSGS) accounted for the majority (25.5%) among primary glomerular diseases while among the secondary glomerular diseases Lupus Nephritis (LN) (51.19%) constituted the majority and a substantial contribution from Human Immunodeficiency Virus Associated Nephropathy (HIVAN). LN was seen only in female patients with a mean age of 33.36 ± 10.74 years. Among LN, Class III was the most predominant while Class IIIC was less frequent. C3 and C4 complement levels were less than normal in Class IV and Class variants of LN. Conclusion: This study highlights the spectrum of Lupus Nephritis and HIV associated nephropathy as a cause for adult NS in a tertiary care center in South India.